SUATU TINJAUAN PEMBATALAN JUAL BELI MENURUT PASAL 1266 DAN 1267 KUH PERDATA - Valensius Higang (Universitas 17 Agustus 1945 Samarinda, 2014)
Abstract That role is now to be run Financial management Posted hearts Against A Comprehensive Control of the Company is: First, financial management Must respect WITH Introduction Sources AGRO And factors affecting the AGRO. Husband Means Financial management should relate to activity Regarding How USING treasure, And From the viewpoint Yang FURTHER, THE process of fund allocation FOR usage hearts Company. Financial management in the Event This is part of a team. The second is the management of funds. Through Process Monitoring liquidity, funding requirements will be known. How funding requirements met husband, Dan of Source APA, will be the most important part of the Company Regarding the Comprehensive Planning. Financial management functions of the Company hearts MAY be considered as a factor Activator For functions functions Implementation of other functions, financial management BECAUSE CAN determine the bounds of possibility To what big hearts the Company's ability to run its activities. Corporate Finance function experienced Developments From time to time, Start of Main functions To get the funds then USE funding problem analysis And Against The flow of funds (Flow of Funds) In perusahaan.Sesuai WITH development functions and understanding hearts Finance Company.